Impact of temperature on gluconic acid production during acetification by Acetobacter aceti - Wiramsri Sriphochanart; Warawut Krusong; Orachon Mekkerdchoo; Rachit Suwapanich; Pongsert Sriprom; Sumate Tantratian (Biotechnology and Applied Biochemistry, 2022)
for protection of the cells against high temperatures. The production of the organic acids, that is, acetic acid, gluconic acid, 2-keto gluconic acid, glucuronic acid, citric acid, succinic acid, lactic acid, and formic acid, was analyzed. Under acetification in the target total concentration of 80 g/L, the highest acetic acid content (39.3 g/L) was obtained at 37°C with an acetification rate of 0.3013 g/L/h, while the acetic acid content and acetification rate achieved at 30°C were 31 g/L and 0.3089 g/L/h, respectively. Additionally, gluconic acid presented at the highest concentration of 2.17 g/L. The rate of production of gluconic acid was 0.0169 g/L/h at 37°C. This acetification process at 37°C will be valuable as an alternative source for gluconic acid production for commercial applications.
Keywords: Microbial metabolism and enzyme function; Microbial Metabolic Engineering and Bioproduction; Biofuel production and bioconversion